IGF-1R Inhibitor Ameliorates Neuroinflammation in an Alzheimer’s Disease Transgenic Mouse Model - Sohrabi, Mona; Floden, Angela M.; Manocha, Gunjan D.; Klug, Marilyn G.; Combs, Colin K. (Frontiers in Cellular Neuroscience, 2020)
Aging is a major risk factor for Alzheimer’s disease (AD). Insulin like growth factor-1 receptor (IGF-1R) regulates general aging and lifespan. However, the contribution of IGF-1 to age-related AD pathology and progression is highly controversial. Based on our previous work, AβPP/PS1 double transgenic mice, which express human mutant amyloid precursor protein (APP) and presenilin-1 (PS-1), demonstrated a decrease in brain IGF-1 levels when they were crossed with IGF-1 deficient Ames dwarf mice (df/df). Subsequently, a reduction in gliosis, amyloid-β (Aβ) plaque deposition, and Aβ1-40/42 concentrations were observed in this mouse model. This supported the hypothesis that IGF-1 may contribute to progression of disease. To assess the role of IGF-1 in AD, 9-10-month-old male littermate control wild type and AβPP/PS1 mice were randomly divided into 2 treatment groups including control vehicle (DMSO) and picropodophyllin (PPP), a selective, competitive, and reversible IGF-1R inhibitor. The brain penetrant inhibitor was given ip. at 1mg/kg/day. Mice were sacrificed after 7 days of daily injection and the brains, spleens, and livers were collected to quantify histologic and biochemical changes. The PPP-treated AβPP/PS1 mice demonstrated attenuated insoluble Aβ1-40/42 and pro-inflammatory cytokine levels in the temporal cortex including eotaxin, TNF-, IL-1, and IL-1. Additionally, an attenuation in microgliosis and protein p-tyrosine levels were observed due to drug treatment in the hippocampus. Our data suggests IGF-1R signaling is associated with disease progression in this mouse model. More importantly, modulation of the brain IGF-1R signaling pathway, even at mid-life, was enough to attenuate aspects of disease phenotype. This suggests that small molecule therapy targeting the IGF-1R pathway may be viable for late stage disease treatment.